The Applicability of Delictual Liability against Pure Economic Loss caused by Negligent Acts: A Sri Lankan Approach - Liyanage, Udapadie S. (My University, 2010)
Patrimonial loss occurred due to physical injury has been redressed by law. In delict, damage or loss is assessed in monetary means and damages are ordered by the court to compensate someone who suffered a legally compensable loss. It requires showing damage done to plaintiff’s patrimony (damnum) or diminution in it caused by defendant’s unlawful and negligent conduct. It does not mean a mere injury to patrimony but includes the actual loss suffered by the plaintiff. In this, it involves actual losses and future or prospective losses that are consequential to patrimonial loss. Accordingly, it is essential to show that the loss is occurred due to any physical damage done by the defendant......